Alumina Surface Treated TiO2 - From Process to Application - Veronovski, Nika (Journal of Coating Science and Technology, 2015)
Titanium dioxide (TiO2) has found widespread use. Typically it is used in another matrix to impart certain properties. For example, it is widely used as a white pigment for paints and polymers. The aim of this research work was to achieve improvements in the sense of processability as well as the dispersion performance of alumina surface treated pigmentary TiO2in polymer matrix. Wet chemical method was used to modify the surface of the TiO2 pigment. Surface treatment included precipitation of hydrous oxides of aluminium on the surface of TiO2 particles. During controlled surface treatment, agglomeration has been avoided, which has been proved to improve applicative properties of TiO2 particles. In addition to that, organic additives were applied to enhance performance attributes of the pigmentary TiO2. The effectiveness of surface treatment was determined using scanning-transmission (STEM) and transmission (TEM) electron microscopy. Quantitative evaluation of quality and dispersion of the pigments has been performed using Filter pressure test. Lower pressure generated during filter pressure test when particles were well dispersed in a polymer matrix. Surface treatment also affected pigment processibility; i.e. filterability and settling, which is of high importance for process planning.